2021
DOI: 10.1002/agj2.20785
|View full text |Cite
|
Sign up to set email alerts
|

Base cation saturation ratios, soil health, and yield in organic field crops

Abstract: Base cation saturation ratio (BCSR) is a soil management philosophy that postulates having an ideal ratio of base cations for maximizing crop yields. This practice is widely used on organic farms, and BCSR practitioners commonly describe improvements in soil health and crop productivity. However, studies evaluating the efficacy of BCSR on soil biological and physical properties are lacking. This 6-yr field study evaluated the effects of changing soil calcium/magnesium (Ca/Mg) ratios on organic corn (Zea mays L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…Of particular importance to BCSR practitioners is the impact of using Ca to displace Mg from exchange sites to improve soil aggregation and physical structure (see Chaganti & Culman, 2017 for in-depth discussion). Using Ca to replace Mg on exchange sites is a fundamental tenet of BCSR practitioners (Brock, Jackson-Smith, Kumarappan, et al, 2021) and has scientific merit, but has not been robustly demonstrated in empirical field experiments to date (Chaganti & Culman, 2017;Chaganti et al, 2021). Future research is needed to better understand how soil type, clay mineralogy, and management practices influence crop and soil responses observed with increasing Ca saturation percentages and the relative roles specific cations (e.g., Ca vs. Mg) play in these responses.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of particular importance to BCSR practitioners is the impact of using Ca to displace Mg from exchange sites to improve soil aggregation and physical structure (see Chaganti & Culman, 2017 for in-depth discussion). Using Ca to replace Mg on exchange sites is a fundamental tenet of BCSR practitioners (Brock, Jackson-Smith, Kumarappan, et al, 2021) and has scientific merit, but has not been robustly demonstrated in empirical field experiments to date (Chaganti & Culman, 2017;Chaganti et al, 2021). Future research is needed to better understand how soil type, clay mineralogy, and management practices influence crop and soil responses observed with increasing Ca saturation percentages and the relative roles specific cations (e.g., Ca vs. Mg) play in these responses.…”
Section: Resultsmentioning
confidence: 99%
“…The soil samples represented a diversity of organic farms, soils, and management practices. Complete details of the study and results are reported in Sprunger et al (2021). Of the 195 soil samples received and analyzed, 58% of these farms said they subscribe to and practice BCSR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, recent reports also recorded perceived positive impacts and long-term use of BCSR among many American farmers (Brock et al 2020;Culman et al 2021) as well as its continuing efficacy studies (Souza et al 2016;Bonomelli et al 2019;Chaganti et al 2021). Some researchers and soil scientists designated that the BCSR approach is also essential in terms of lime, gypsum, soil acidity, and cation competition study (Webster 1985;van Biljon et al 2007;Wood & Litterick, 2017;Culman et al 2021).…”
Section: Soil Fertility Statusmentioning
confidence: 99%